Investigation of Stent Prototypes for the Eustachian Tube in Human Donor Bodies - Lena Rosenbusch; Robert Schuon; Tamara Wilfling; Philipp Krüger; Kerstin Lebahn; Samuel John; Olga Sahmel; Niels Grabow; Marko Schulze; Andreas Wree; Klaus-Peter Schmitz; Tobias Stein; et al. (Bioengineering, 2023)
Chronic otitis media is often connected to Eustachian tube dysfunction. As successful treatment cannot be guaranteed with the currently available options, the aim is to develop a stent for the Eustachian tube (ET). Over the course of this development, different prototypes were generated and tested in ex vivo experiments. Four different prototypes of an ET stent and one commercially available coronary stent were implanted in the ET of seven human donor bodies. The position of the stents was verified by cone beam CT. The implanted ETs were harvested, embedded in resin and ground at 200 µm steps. Resulting images of the single steps were used to generate 3D models. The 3D models were then evaluated regarding position of the stent in the ET, its diameters, amount of squeezing, orientation of the axes and other parameters. Virtual reconstruction of the implanted ET was successful in all cases and revealed one incorrect stent placement. The cross-section increased for all metal stents in direction from the isthmus towards the pharyngeal orifice of the ET. Depending on the individual design of the metal stents (open or closed design), the shape varied also between different positions along a single stent. In contrast, the cross-section area and shape remained constant along the polymeric prototype. With the current investigation, insight into the behavior of different prototypes of ET stents was gained, which can help in defining the specifications for the intended ET stent.